Myocardial remodelling and tissue characterisation by cardiovascular magnetic resonance (CMR) in endurance athletes. Issue 1 (25th October 2018) - Pujadas, Sandra; Doñate, Maite; Li, Chi-Hion; Merchan, Soraya; Cabanillas, Ana; Alomar, Xavier; Pons-Llado, Guillem; Serra-Grima, Ricard; Carreras, Francesc
Abstract : There is still some controversy about the benignity of structural changes observed in athlete's heart, especially regarding the observation of increased biomarkers and the presence of myocardial fibrosis (MF). Aim: Our purpose was to evaluate by cardiovascular magnetic resonance (CMR) the presence of diffuse as well as focal MF in a series of high-performance veteran endurance athletes. Methods: Thirty-four veteran healthy male endurance athletes, still being in regular training, with more than 10 years of training underwent a CMR. A cardiopulmonary exercise test was also performed to assess their maximal physical performance. The control group consisted in 12 non-trained normal individuals. Results: We found an increase in both, right and left ventricular (LV) volumes in the athlete's group when compared with controls. There was no increase in indexed LV myocardial mass despite of a significantly increased maximal myocardial wall thickness in comparison to controls. Native T1 values and extracellular volume (ECV) were normal in all cases. We did not find differences in native T1 values and ECV between both groups. In three athletes (9%), non-ischaemic late gadolinium enhancement (LGE) was observed. We did not find a correlation between total training volume and presence of LGE or with the ECV value. Conclusions: Our results show that the majority of veteran endurance athletes present with myocardial remodelling without MF as a physiological adaptive phenomenon. In the only three athletes with focal MF, the LGE pattern observed suggests an intercurrent event not related with the remodelling phenomenon.